Motion Verbs in Adventure Tourism: A Lexico-Semantic Approach to Fictive Meaning - Durán-Muñoz, Isabel; Jiménez-Navarro, Eva Lucía (International Journal of English Studies, 2023)
This paper investigates the terminological value of motion verbs in the specialized discourse of adventure tourism, being the primary focus placed on fictive meaning. Thus, we will delve into the participants surrounding motion verbs in context, given that the former activate the latter’s specialized meaning and are key to discover the type of motion represented. With this objective in mind, we will adopt a corpus-driven methodology and a lexico-semantic approach, following these steps: (1) the compilation of a specialized English corpus, (2) the automatic extraction of a list of candidate verbs and their manual verification, and (3) their categorization according to the type of motion depicted, that is, real, fictive or both. The main findings show that, despite having found a greater representation of real motion in this discourse, verbs denoting fictive motion were worth examining, as 50% of the results inferred at least one example of this type.